MENINGKATKAN HASIL BELAJAR PKn MATERI INTEGRASI NASIONAL DALAM BINGKAI BHINEKA TUNGGAL IKA MELALUI METODE DISKUSI SISWA KELAS X MIPA-1 SMA NEGERI 1 SIGLI TAHUN PELAJARAN 2021/2022 - Ruslan Ruslan (Jurnal Sains Riset, 2022)
This type of research is classroom action research (CAR). The CAR model used is the spiral model from Kemmis, S. and Mc Taggart, R using 2 cycles, each cycle consisting of 4 stages, namely planning, implementing actions and observing, reflecting. The research subjects were 35 students of class X MIPA-1 SMA Negeri 1 Sigli. Data collection techniques with test techniques and nontest techniques which include observation techniques and observation techniques. As for the research instrument by using item questions, observation sheets. The analytical technique used is descriptive quantitative which includes the number, mean, minimum-maximum score, percentage and graph/diagram. The research was carried out at SMA Negeri 1 Sigli, Pidie Regency, Aceh Province, for the 2021/2022 academic year in Class X MIPA-1 whose learning achievement was still low. The purpose of this classroom action research is to find out whether the application of the Quantum Learning Model can improve student learning achievement. This classroom action research was conducted in two cycles through the stages of planning, implementing, observing and reflecting. Learning achievement test is a tool used in collecting research data which is then analyzed using descriptive analysis. The results obtained from this study indicate an increase in the ability of students to follow the learning process from an initial average of 68.85 increased to 74.42 in the first cycle and increased to 90.28 in the second cycle with an initial learning completeness of 28.57% in the first cycle. I increased to 68.57% and in the second cycle increased to 97.14%. The conclusion that can be drawn from these results is that the application of the quantum learning model in the implementation of the learning process is able to improve student learning outcomes.Keywords: PPKn Learning Discussion Method, Learning Outcomes